Warlord Yen Hsi-Shan in Shansi Province, 1911-1949 - Gillin, Donald G. (Princeton Legacy Library, 2016)
This is an inquiry into the dynamics of local and regional government in China, as illustrated by the policies of the warlord Yen Hsi-shan. The schemes Hsi-shan tried to carry out in Shansi constitute one of the last systematic attempts in China to bring about reform along conservative lines.Originally published in 1967.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905